Retroiliac ureter presenting as right upper ureteric obstruction – report of a rare case - Prasad, Honderabalu Lingaraju; Karthikeyan, Vilvapathy Senguttuvan; Shivalingaiah, Maregowda; Ratkal, Chandrashekar S. (International Journal of Research in Medical Sciences, 2017)
Retroiliac ureter is an extremely rare urological entity in which the ureter passes deep to the iliac vessels. Congenital causes are most often secondary to vascular variants. A 39 year old lady presented with one month history of right loin pain. CECT showed right gross HUN till L3 and EC renogram showed 33% function in right kidney with obstructive pattern. RGP revealed Right Pelvic Ureteric Junction Obstruction (PUJO) obstruction, but at exploration was found to have retroiliac ureter. Ureteral division with anterior relocation and dismembered pyeloplasty was done. Anomalous vascular structures are often not diagnosed until surgical intervention for an obstruction of unknown etiology, unless vascular studies are considered, Most of these patients require surgical exploration to exclude tubercular stricture or malignant process.